A distinct expression of various gene subsets in CD34+ cells from patients with early and advanced myelodysplastic syndrome - Vasikova, Alzbeta; Belickova, Monika; Budinska, Eva; Cermak, Jaroslav (Leukemia research, 2010)
Gene expression profiles of CD34+ cells were compared between 51 MDS patients and 7 controls. The most up-regulated genes in patients included HBG2, HBG1, CYBRD1, HSPA1B, ANGPT, and MYC, while 13 genes related to B-lymphopoiesis showed down-regulation. We observed in advanced MDS patients decreased expression of genes involved in cell cycle control, DNA repair and increased expression of proto-oncogenes, angiogenic and anti-apoptic genes. The results suggest that increased cell proliferation and resistance to apoptosis together with a loss of cell cycle control, damaged DNA repair and altered immune response may play an important role in malignant clone expansion in MDS.
Keywords: senioři; cytochromy typu b; Cell Cycle; DNA Damage; apoptóza; angiopoetin-1; Gene Expression Regulation; poškození DNA; Middle Aged; HSP70 Heat-Shock Proteins; Myelodysplastic Syndromes; mužské pohlaví; Antigens, CD34; Adult; Oncogene Protein p55(v-myc); buněčný cyklus; regulace genové exprese; myelodysplastické syndromy; Angiopoietin-1; ženské pohlaví; Humans; Oxidoreductases; oprava DNA; lidé středního věku; onkogenní protein p55(v-myc); dospělí; antigeny CD34; DNA Repair; Female; proteiny tepelného šoku HSP70; Aged; Cytochrome b Group; lidé; Male; Apoptosis; oxidoreduktasy